The Pivotal Role of Students in International Psychology: A Past, Present, and Future Overview - Daniel Balva; Harold Takooshian (RUDN Journal of Psychology and Pedagogics, 2022)
In 2022, the American Psychological Association’s (APA) Division 52 (International Psychology) marked the long-anticipated 25th anniversary of its foundation on February 21, 1997. This is an apt time to review the important and often overlooked roles of students within international psychology. This concise, yet panoramic overview explores the roles of students in international psychology, in APA’s Division 52, and in student-led organizations in five parts: (1) prehistory of Division 52 prior to 1997; (2) early years of Division 52; (3) recent years of Division 52; (4) the current rise of a new studentled organization; (5) future directions for international psychology.